1B.003 Getting It Right – Wsnz M&x0101;ori Strategy Refresh. (14th March 2021) - McInnes, Neil
Abstract : Context: M&x0101;ori are over-represented In New Zealand's drowning statistics. Water Safety New Zealand (WSNZ) has had a several iterations of a strategy to guide targeted water safety interventions for M&x0101;ori. The results of these strategies has been mixed. Process: In May 2018 WSNZ bought together key M&x0101;ori water safety experts and practitioners to discuss a refresh of WSNZ's M&x0101;ori strategy. WSNZ indicated it wanted to improve its capability to work with M&x0101;ori. Hui participants noted they had 'been here before' but agreed to work in partnership with WSNZ as an advisory group on the M&x0101;ori strategy refresh. This included formalising their relationship with WSNZ through a Memorandum of Understanding for a 12-month trial period with a set of objectives and activities that could be realistically achieved. Analysis: The M&x0101;ori strategy refresh project focused on what could be done to improve WSNZ's performance for M&x0101;ori, not develop a water safety sector M&x0101;ori strategy per se. However it enabled a wider discussion about WSNZ's desired drowning prevention outcomes for M&x0101;ori and how these could be achieved. Outcomes: Towards the end of 2019 a series of workstreams for WSNZ were agreed with the M&x0101;ori advisory group around: WSNZ's internal capability in Te Ao M&x0101;ori; WSNZ's relationships with M&x0101;ori; and drowning prevention initiatives for M&x0101;ori. Learning Outcomes: The key learnings for WSNZ have been about getting the process right; taking the time required to get agreement; being honest about your capability (or lack of it); and the necessity of showing commitment to working together.